The Value of Preoperative Plasma VEGF Levels in Urothelial Carcinoma of the Bladder Treated with Radical Cystectomy - Mori, Keiichiro; Schuettfort, Victor M; Katayama, Satoshi; Laukhtina, Ekaterina; Pradere, Benjamin; Quhal, Fahad; Sari Motlagh, Reza; Mostafaei, Hadi; Grossmann, Nico C; Rajwa, Pawel; König, Frederik; Aydh, Abdulmajeed; et al. (European urology focus, 2022)
BACKGROUND: Elevated preoperative plasma levels of the angiogenesis-related marker VEGF have been associated with worse oncological outcomes in various malignancies. OBJECTIVE: To investigate the predictive/prognostic role of VEGF in patients with urothelial carcinoma of the bladder (UCB) treated with radical cystectomy (RC). DESIGN, SETTING, AND PARTICIPANTS: VEGF plasma levels were measured preoperatively in 1036 patients with UCB who underwent RC. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: The correlation between plasma VEGF levels and pathological and survival outcomes was assessed using logistic regression and Cox regression analyses. Discrimination was assessed using the concordance index (C index). The clinical net benefit was evaluated using decision curve analysis (DCA). RESULTS AND LIMITATIONS: Patients with higher pretreatment plasma VEGF levels had poorer recurrence-free survival (RFS), cancer-specific survival (CSS), and overall survival (OS) according to log-rank tests (all p < 0.001). Higher VEGF levels were not independently associated with higher risk of lymph node metastasis, ≥pT3 disease, or non-organ-confined disease (all p > 0.05). Preoperative plasma VEGF levels were independently associated with RFS, CSS, and OS in preoperative and postoperative multivariable models. However, in all cases the C index increased by <0.02 and there was no improvement in net benefit on DCA. A limitation is that none of the patients received current elements of standard of care such as neoadjuvant chemotherapy. CONCLUSIONS: Elevated plasma VEGF levels were associated with features of biologically and clinically aggressive disease such as worse survival outcomes among patients with UCB treated with RC. However, VEGF appears to have relatively limited incremental additive value in clinical use. Further study of VEGF for UCB prognostication is warranted before routine use in clinical algorithms. PATIENT SUMMARY: Currently available models for predicting outcomes in bladder cancer are less than optimal. A protein called vascular endothelial growth factor (VEGF), which is a marker of the formation of blood vessels (angiogenesis), may have a role in predicting survival outcomes in bladder cancer.
Keywords: nádory močového měchýře; Radical cystectomy; Cystectomy; močový měchýř; Urothelial carcinoma of the bladder; vaskulární endoteliální růstový faktor A; Vascular Endothelial Growth Factor A; Vascular endothelial growth factor; cystektomie; Urinary Bladder Neoplasms; lidé; Urinary Bladder; Biomarker; Humans; karcinom z přechodných buněk; Carcinoma, Transitional Cell